Design and Implementation Smart Home Alarm System with Zigbee transceiver - Jameel Hadi, Hadi; Khudhur Hussein, Zaid; Mahmod Lafta, Waail; Kareem Alammar, Zaenab; Almaarofi, Huda (International Journal of Engineering and Technology, 2018)
The smart house system is a significant area for the Internet of Things (IoT) with appropriate demands that structure for the smart home usages. The proposal for the smart home system (HCS) via IoT built in XBee is presented in this paper. The system design uses XBee wireless technique communications, which is able to send and receive the transmission data between the central controller unit and various house sensor nodes to reading and sending Temperature, Gas Sensing and IR Security information. The tested results illustration the wireless monitoring usage for the ability is recognized. The control proposed system design is simple and achievable, which can be used for smart house remote monitoring extensively.
Keywords: House Control System (HCS); Wireless Sensor Network (WSN); ZigBee; Arduino.